The Influence of Brand Image and Brand Trust on Purchase Decisions Through Consumer Trust as Intervening Variables in N'cip Roti - Anggi Arista Irawanto; Nersiwad Nersiwad; Kasnowo Kasnowo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The fierceness of today's business battles requires business actors to be able to win the competition to achieve the goals that have been planned. Therefore, they must know what factors can influence consumer purchasing decisions. Brand image, brand trust and consumer trust are factors that can influence purchasing decisions. The research aims to determine the effect of brand image and brand trust on purchasing decisions through consumer trust as an intervening variable in N'cip Roti. The research was conducted by distributing questionnaires via Google form to consumers. The population in this study are consumers who make purchases at N'cip Roti. The sample of this research is 80 with purposive sampling technique. Data analysis techniques using SmartPLS 3.2.9. The results of this study indicate that the brand image variable has no effect on purchasing decisions, brand trust has an effect on purchasing decisions, consumer trust has an effect on purchasing decisions, brand image has no effect on purchasing decisions through consumer trust, brand trust has an effect on purchasing decisions through consumer trust in N’cip Roti.